Double or die : a James Bond adventure - Higson, Charles, 1958-; Fleming, Ian, 1908-1964. (New York : Disney/Hyperion Books, 2009)
Teenage James Bond is on the case when a professor is kidnapped in a north London cemetery, and an encoded letter arrives which, once deciphered, leaves James with just forty-eight hours to rescue the captured scholar and save the world.
6.4
5-8
5-8.
School Library Journal
New York Times
Horn Book
Keywords: Bond, James (Fictitious character) -- Juvenile fiction; Kidnapping -- Juvenile fiction; Bond, James (Fictitious character) -- Fiction; Spies -- Fiction; Kidnapping -- Fiction; Adventure and adventurers -- Fiction; Mystery and detective stories; Bond, James (Fictional character) -- Fiction; Spy stories; Kidnapping -- Fiction; Adventure fiction; Mystery fiction; Adventure fiction; Mystery fiction